2014
DOI: 10.1021/ja4092038
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Nuclear Polarization Enhanced NMR Spectroscopy for Pharmaceutical Formulations

Abstract: Dynamic nuclear polarization (DNP) enhanced solid-state NMR spectroscopy at 9.4 T is demonstrated for the detailed atomic-level characterization of commercial pharmaceutical formulations. To enable DNP experiments without major modifications of the formulations, the gently ground tablets are impregnated with solutions of biradical polarizing agents. The organic liquid used for impregnation (here 1,1,2,2-tetrachloroethane) is chosen so that the active pharmaceutical ingredient (API) is minimally perturbed. DNP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
211
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(213 citation statements)
references
References 91 publications
1
211
1
Order By: Relevance
“…as an alternative method for the structural analysis of APIs. 11,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Our research group and others have demonstrated that 35 Cl SSNMR can function as a non-destructive structural probe and a technique for polymorph identification and screening of hydrochloride (HCl) APIs. [36][37][38][39] Given that more than 50% of APIs are produced as HCl salts, 40 the widespread use of 35 Cl SSNMR in quality assurance, and research and development departments of pharmaceutical companies is promising.…”
Section: Introductionmentioning
confidence: 99%
“…as an alternative method for the structural analysis of APIs. 11,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Our research group and others have demonstrated that 35 Cl SSNMR can function as a non-destructive structural probe and a technique for polymorph identification and screening of hydrochloride (HCl) APIs. [36][37][38][39] Given that more than 50% of APIs are produced as HCl salts, 40 the widespread use of 35 Cl SSNMR in quality assurance, and research and development departments of pharmaceutical companies is promising.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, relayed DNP was shown to be a general method to polarize microcrystalline organic solids, including pharmaceuticals. [46][47][48] Alternatively, DNP NMR was performed on amorphous solid dispersions (ASD) of pharmaceuticals and polymers by directly incorporating the PA during synthesis. 49 Relayed DNP has enabled a number of challenging solid-state NMR experiments on organic solids including natural isotopic abundance 2D double-quantum 13 C-13 C correlation ( Figure 5C Sn solid-state NMR spectra of Sn-β catalysts prepared by different synthetic procedures illustrate that the sample preparation greatly affects the distribution of tin-sites within the zeolite framework ( Figure 5D).…”
mentioning
confidence: 99%
“…In another more extensive study, the crystalline and amorphous forms of cetirizine, povidone (excipient), as well as four brands of cetirizine tablet formulations (Life, CVS, Reactine and Wal-Zyr) were analysed by both 13 C and 15 N CP/MAS NMR under DNP (Fig. 2) [9].…”
Section: Dynamic Nuclear Polarization (Dnp) Enhanced Nmrmentioning
confidence: 99%